Evaluación de la viabilidad técnico financiera para la obtención de un colorante natural partiendo del residuo mora de castilla (Rubus Glaucus Benth) para la aplicación en la industria de alimentos (2019)
In this project are the blackberry residue for the production of a natural dye, this pigment is characterized by containing anthocyanins, an important component that generates a characteristic red hue. To obtain it, three extraction methods are used, such as: soxhlet, ultrasound and microwave. In the case of soxhlet and ultrasound extraction, ethanol in different variables in aqueous medium were analyzed as main analyzes. The extracts were characterized by means of an acid base test and quantification of anthocyanins, these analyzes were performed to identify the best method of extraction and the concentration of ethanol that led to the highest yield. Among the soxhlet and ultrasound extraction method, it was identified that, in terms of yield and amount of total anthocyanins, the best is the soxhlet extraction using as ethanol 96% (v / v), in which 1413,839 ± 4.20 mg were obtained of cyanidin-3-glucoside / 100g of blackberry residue.